Pengaruh Kesadaran Wajib Pajak Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak UMKM - Madjodjo, Farid; Baharuddin, Ilfan (Universitas Gorontalo, 2022)
This study aims to determine the effect of taxpayer awareness and tax service services taxpayer oncompliance UMKM in the City of Tidore Islands either partially or simultaneously. This type of research is quantitative research with a causal approach, while the source of data used is primary data obtained from the results of distributing questionnaires. The questionnaire was measured using ascale Likert five-pointwhich was graded from very positive to very negative. Technique uses the sampling Probability Sampling with the method Simple Random Sampling. The method of data analysis used multiple linear regression analysis.The results of the study prove that either partially or simultaneously the awareness of taxpayers and the service of the tax authorities has a significant and positive effect on taxpayer compliance UMKM in the City of Tidore Islands. This shows that the better the level of awareness of taxpayers and good tax service services by tax officials, it can increase taxpayer compliance in paying and reporting their tax obligations in accordance with applicable regulations